The Effect of Information Technology Utilization and Information System User Participation on System Performance Payroll - Dalimunthe, Mohd.Idris (LLDIKTI Wilayah 1 Sumatera Utara, 2021)
Every company has a payroll system that is designed in such away. Payroll system design is in line with system users. If the payroll system design is correct but the users are still difficult to run the system, it will complicate the decision-making process in the payroll.This study aims to determine the effect of the use of information technology and the participation of users of information systems on the performance. Types of associative research. The population of this research is all employees involved in the payroll process. Sampling using purposive sampling method of 35 respondents. Data processing using SPSS software. The results show that the use of information technology has a positive and significant effect on the performance of the payroll system. Information system user participation has a positive and significant effect on the performance of the payroll system. The use of information technology and the participation of information system users have a positive and significant effect on the performance of the payroll system.